The Geography of Crime: Exploring Spatial Distribution and Environmental Criminology - Balaselvakumar, S.; Santhi, P. Mary (The Geography of Crime: Exploring Spatial Distribution and Environmental Criminology, 2025)
The Geography of Crime is an emerging interdisciplinary field that integrates criminology and geography to explore the spatial patterns, causes, and consequences of criminal activity. This book provides an extensive analysis of how crime is distributed across different geographical regions and how socio-economic, cultural, environmental, and political factors influence such distribution. It emphasizes the significance of spatial analytical techniques such as Geographic Information Systems (GIS), crime mapping, and spatial regression in understanding crime hotspots and developing effective prevention strategies. The theoretical foundations, including environmental criminology, social disorganization theory, routine activity theory, and crime pattern theory, offer robust frameworks for explaining the interaction between human behavior and the physical and social environment. The book also highlights methodological approaches and data sources vital to crime research, alongside discussions on various crime types—ranging from violent and property crimes to cybercrime, hate crime, and environmental offenses. Special attention is given to the Indian context and international perspectives, showcasing localized insights and global patterns. This work serves as a crucial resource for researchers, urban planners, policymakers, and law enforcement agencies aiming to build safer, more equitable societies through geographically informed crime prevention strategies.